2010
DOI: 10.1371/journal.pone.0014076
|View full text |Cite
|
Sign up to set email alerts
|

IFN-γ Upregulates Survivin and Ifi202 Expression to Induce Survival and Proliferation of Tumor-Specific T Cells

Abstract: BackgroundA common procedure in human cytotoxic T lymphocyte (CTL) adoptive transfer immunotherapy is to expand tumor-specific CTLs ex vivo using CD3 mAb prior to transfer. One of the major obstacles of CTL adoptive immunotherapy is a lack of CTL persistence in the tumor-bearing host after transfer. The aim of this study is to elucidate the molecular mechanisms underlying the effects of stimulation conditions on proliferation and survival of tumor-specific CTLs.Methodology/Principal FindingsTumor-specific CTLs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
44
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 61 publications
(92 reference statements)
2
44
0
Order By: Relevance
“…It is a critical intracellular machinery of cytokines involved in gene expression and cellular activation, proliferation and differentiation [12,13]. IFN-γ has been found to activate the expression of target genes through binding of activated STAT1 proteins on a consensus element termed the IFN-γ-activated site (GAS) [15,16]. It has been shown that upon stimulation of IFN-γ, JAKs are activated and phosphorylate STAT1that shapes a homodimer and moves into the nucleus binding to GASs within promoters of target gene [5,15,16].…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…It is a critical intracellular machinery of cytokines involved in gene expression and cellular activation, proliferation and differentiation [12,13]. IFN-γ has been found to activate the expression of target genes through binding of activated STAT1 proteins on a consensus element termed the IFN-γ-activated site (GAS) [15,16]. It has been shown that upon stimulation of IFN-γ, JAKs are activated and phosphorylate STAT1that shapes a homodimer and moves into the nucleus binding to GASs within promoters of target gene [5,15,16].…”
mentioning
confidence: 99%
“…IFN-γ has been found to activate the expression of target genes through binding of activated STAT1 proteins on a consensus element termed the IFN-γ-activated site (GAS) [15,16]. It has been shown that upon stimulation of IFN-γ, JAKs are activated and phosphorylate STAT1that shapes a homodimer and moves into the nucleus binding to GASs within promoters of target gene [5,15,16]. Intriguingly, it has been reported that IFN-γ is a transcriptional inducer of survivin gene in an autocrine manner through STAT1 pathway [16].…”
mentioning
confidence: 99%
See 3 more Smart Citations